PAPR Analysis of OFDM using Partial Transmit Sequence Method - Vamshi, Rama Raja; Shivani, Aitha; Siddharatha, Thipparapu; Kavya, Mardha (Journal of ISMAC, 2022)
Orthogonal Frequency Division Multiplexing (OFDM) is one of the most widely used multicarrier transmission and effective technologies in today's communication networks. OFDM has many benefits and drawbacks. High Peak to Average Power Ratio (PAPR) is one of its main drawbacks. The spectral efficiency of the high-power amplifiers decreases with increasing PAPR. Therefore, maintaining a wireless system's efficiency is required to lower the PAPR. A possible method for lowering the high PAPR in OFDM systems is Partial Transmit Sequence (PTS). PTS generates a number of candidate signals, and the best signal with the lowest PAPR is chosen for transmission. The results shows that the PTS technique achieves greater PAPR minimization with less complexity. MATLAB simulation has been used to examine the OFDM system's PSD, spectral efficiency, BER performance, and PAPR analysis.
Keywords: PAPR; OFDM; PTS; BER; SNR; PSD